2007
DOI: 10.1113/jphysiol.2007.141671
|View full text |Cite
|
Sign up to set email alerts
|

α2‐Noradrenergic receptors activation enhances excitability and synaptic integration in rat prefrontal cortex pyramidal neurons via inhibition of HCN currents

Abstract: Stimulation of α 2 -noradrenergic (NA) receptors within the PFC improves working memory performance. This improvement is accompanied by a selective increase in the activity of PFC neurons during delay periods, although the cellular mechanisms responsible for this enhanced response are largely unknown. Here we used current and voltage clamp recordings to characterize the response of layer V-VI PFC pyramidal neurons to α 2 -NA receptor stimulation. α 2 -NA receptor activation produced a small hyperpolarization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 55 publications
10
94
2
Order By: Relevance
“…An alternative modulation of HCN channels by a 2 -adrenoceptors in prefrontal neurons has been proposed by a different group [156]. Carr et al suggest that a 2 -adrenoceptor activation suppresses HCN channels in prefrontal neurons through a signalling pathway that does not appear to involve cAMP, but appears to be mediated by PLC-PKC signalling.…”
Section: H Controls Working Memorymentioning
confidence: 97%
“…An alternative modulation of HCN channels by a 2 -adrenoceptors in prefrontal neurons has been proposed by a different group [156]. Carr et al suggest that a 2 -adrenoceptor activation suppresses HCN channels in prefrontal neurons through a signalling pathway that does not appear to involve cAMP, but appears to be mediated by PLC-PKC signalling.…”
Section: H Controls Working Memorymentioning
confidence: 97%
“…Carr et al (71) suggested that ␣ 2 -adrenoceptor activation suppresses HCN channels in prefrontal neurons through a cAMP-independent signaling pathway that appears to be mediated by PLC-PKC signaling.…”
Section: Role Of I H In Working Memorymentioning
confidence: 99%
“…The combination of synaptic enhancement (via effects on dendritic I h ) with membrane hyperpolarization (via effects on somatic I h ) provides a background in which isolated synaptic inputs are less effective, whereas effects of synchronous excitatory synaptic potentials are enhanced. In general, this situation would favor coherent oscillatory behavior (Carr et al 2007) and, indeed, decreases in I h have been observed in a number of epilepsy models in rodents (Jung et al 2007;Kole et al 2007;Shah et al 2004).…”
Section: Anesthetics Enhance Epsp Summation In Cortical Neurons By Inmentioning
confidence: 99%